Mastering IIS7 implementation and administration - Mueller, John (Wiley Pub., 2007)
Microsoft's IIS 7 is a radical departure from previous versions, and it promises administrators a new level of control over their Web servers. This book guides you beyond the networking technology and concepts you already know and teaches you the crucial new features of IIS 7 that will help you succeed with this dramatically different Web server. From navigating the new interface to configuring IIS 7 for maximum security and more, this book covers the techniques, tricks, and basic instruction you need.